SILAC-based quantitative proteomics and microscopy analysis of cancer cells treated with the N-glycolyl GM3-specific anti-tumor antibody 14F7 - Bousquet, Paula A.; Manna, Dipankar; Sandvik, Joe A.; Arntzen, Magnus Ø.; Moreno, Ernesto; Sandvig, Kirsten; Krengel, Ute (Frontiers in Immunology, 2022)
Cancer immunotherapy represents a promising approach to specifically target and treat cancer. The most common mechanisms by which monoclonal antibodies kill cells include antibody-dependent cell-mediated cytotoxicity, complement-dependent cytotoxicity and apoptosis, but also other mechanisms have been described. 14F7 is an antibody raised against the tumor-associated antigen NeuGc GM3, which was previously reported to kill cancer cells without inducing apoptotic pathways. The antibody was reported to induce giant membrane lesions in tumor cells, with apparent changes in the cytoskeleton. Here, we investigated the effect of humanized 14F7 on HeLa cells using stable isotope labeling with amino acids in cell culture (SILAC) in combination with LC-MS and microscopy. 14F7 did not kill the HeLa cells, however, it caused altered protein expression (MS data are available via ProteomeXchange with identifier PXD024320). Several cytoskeletal and nucleic-acid binding proteins were found to be strongly down-regulated in response to antibody treatment, suggesting how 14F7 may induce membrane lesions in cells that contain higher amounts of NeuGc GM3. The altered expression profile identified in this study thus contributes to an improved understanding of the unusual killing mechanism of 14F7.